Complexité et défis associés aux rôles de conseiller pédagogique - Duchesne, Claire (McGill Journal of Education / / Revue des sciences de l’éducation de McGill, 2016)
Pedagogical advisors working at the school board level accomplish their mission by taking on a diversity of professional roles. A literature review and testimonials from 11 pedagogical advisors working for a francophone school board in Ontario highlight eight professional roles. The challenges faced by the participants while exercising each of these roles were further elaborated in research interviews. Specific issues associated to the roles of change agent, reflexive practitioner, and manager are further discussed.